a: \(x\in\left[-2;3\right]\)
nên \(\left\{{}\begin{matrix}x^4\in\left[0;81\right]\\x^2\in\left[0;9\right]\end{matrix}\right.\Leftrightarrow x^4+3x^2\in\left[0;108\right]\)
=>\(y\in\left[2;110\right]\)
y=2 khi x=0
y=110 khi \(x^4+3x^2=108\)
=>x^4+12x^2-9x^2-108=0
=>x=3
c: \(y=x\left(x+3\right)\left(x+1\right)\left(x+2\right)\)
\(=\left(x^2+3x\right)\left(x^2+3x+2\right)\)
\(=\left(x^2+3x\right)^2+2\left(x^2+3x\right)+1-1\)
\(=\left(x^2+3x+1\right)^2-1>=-1\)
Dấu'=' xảy ra khi x^2+3x+1=0
hay \(x\in\left\{\dfrac{-3+\sqrt{5}}{2};\dfrac{-3-\sqrt{5}}{2}\right\}\)